Abu Al-Fida 's curriculum in his abbrive book in the news of the people about the Umayyad state as a model - Chnaitr, Mohamed Abd El-Rida (Al-Adab Journal, 2021)
This research deals with the approach of the historian Abu al-Fida Imad al-Din Ismail bin Ali (d. 732 AH / 1332 AD) on the history of the Umayyad state through his book (The Brief Fi Akhbar al-Bishr), where the research was made of historical sources and resources and the method he used in writing this section, noting that Researchers have studied studies about his personality and his book (Al-Mukhtasar fi Akhbar Al-Bishr), but they did not give this section (the Umayyad state) a full and detailed study of his methodology and resources, and this is what we will prove through our research, that this study has necessarily relied on the book (Al-Mukhtasar fi Akhbar). humans), as a source for it, and therefore the benefit from other sources has diminished in many places and in a wide area of ​​them, and from this logic we tried to do a scientific study on this subject and chose Abu Al-Fida as one of the historians who developed a special approach in his writing of history, which was reflected in his writing For the Umayyad state, this study aims to reveal and clarify Abu al-Fida’s approach to writing the history of the Umayyad state. This is what he used to record the events of the Umayyad dynasty.